An investigation of the effect of wide range Gamma radiation from nanoindentation of the SAC305 solder alloy - Rosman, Muhammad Nur Hisyam; Wan Yusoff, Wan Yusmawati; Manaf, Nor Azlian Abdul; Abdullah, Mohamad Faizal; Che Abdullah, Che Azurahanim; Zyoud, Samer H. (Penerbit Akademia Baru, 2024)
This study utilises nanoindentation testing to investigate the impact of varying gamma radiation doses on the micromechanical properties of Sn-Ag-Cu (SAC) alloy. Specifically, the focus is on evaluating changes in hardness, reduced modulus, and creep behaviour. The stencil-printed method and reflow soldering process were employed to apply the SAC solder paste and create solder joints on the surface of the printed circuit board. The soldered samples underwent exposure to gamma radiation at different doses, specifically 5, 50, 500, 5000, and 50000 Gy. The solder received in its original state was used as the control sample. Subsequently, the samples were subjected to a nanoindentation test in order to ascertain the correlation between load and depth, depth and dwell time, when exposed to radiation. The load-depth curve results indicate that there is a transition in the behaviour of solder joint materials from elastic to plastic deformation as the radiation dose increases. A finding has been made indicating that exposure to gamma radiation has the potential to induce a transition in the behaviour of SAC from an elastic state to a plastic state. The exposure to radiation doses has been found to induce changes in the atomic arrangement and structural properties of materials, leading to an increase in their hardness values. Nevertheless, it was observed that with increasing radiation doses up to 500 Gy, there was a noticeable decrease in the hardness value, which can be attributed to the occurrence of softening behaviour. Exposure to a high dose exceeding 5000 Gy leads to atomic displacement and transmutation products, subsequently resulting in plastic deformation. The stress exponent value signifies the occurrence of the deformation mechanism in solder material when exposed to gamma radiation. The study revealed that there was a shift in the deformation mechanism from grain boundary sliding to dislocation climb as the radiation dose increased from low to high levels. © 2024, Penerbit Akademia Baru. All rights reserved.